Colorimetric method to determine the rancidity of oils and solid fats - Oliver, J.; Suñé, J.Mª. (Ars Pharmaceutica (Internet), 1965)
An original colorimetric technique is established to determine the degree of rancidity of a grease that allows an autoxidation process to be advantageously advantageous compared to the techniques used up to now and without any interference being demonstrated at the moment.